Internet and Regulation: ICANN in Light of the Theory of Regulation - Bianchi, José Flávio (Law, State and Telecommunications Review, 2016)
Purpose ”“ The main goal of the paper is to analyze ICANN’s activities, a non-profit corporation with regulatory role, in light of a specific theory of regulation. Methodology/approach/design ”“ The methodology includes the analysis of the material published by ICANN during the expansion of the gTLD programme, in special the ruling related to the “.amazon” gTLD. Findings ”“ The activities of ICANN fits into the framework of the administrative process theory. Originality/value ”“ This paper innovates in the analysis of a purely privately-held entity ”“ i.e. ICANN, although it has ties with the U.S. government ”“ from the perspective of the administrative process theory of regulation.